Analisis Faktor Pendorong Adaptasi Suku Bajo pada Kegiatan Usahatani di Desa Jawi-Jawi Kecamatan Bungku Selatan Kabupaten Morowali - Batoa, Hartina; Mardin, Mardin; Dahlan, Dahlan (Jurnal Ilmiah Membangun Desa dan Pertanian, 2020)
The research was conducted in Jawi-Jawi Village, Bungku Selatan Subdistrict, Morowali Regency from February to March 2019. The location selection was carried out purposively deliberately) with the consideration that the people are Bajo people who work as fishermen. The determination of informants was carried out using the census method, totaling 8 people, and had carried out farming activities, consisting of Bajo ethnic fishermen, village heads, village secretaries, and community leaders. Collecting data using observation techniques, in-depth interviews, and documentation. Retrieval of data through interviews with informants based on a list of questions and related parties in farming activities. The data analysis used is descriptive qualitative analysis. The results showed that the factors driving the adaptation form of the Bajo tribe to farming activities were internal factors, namely the lack of income of fishermen, lack of fishing gear, lack of knowledge of fishermen, age of fishermen, and limited capital. Meanwhile, external factors are uncertain climatic conditions and the impact of mining activities.